Systematic Analysis of IoT, AI, Active Packaging, and Blockchain for Food Waste Reduction across the Farm-to-Fork Supply Chain - Simon Suwanzy Dzreke (Sultan Publisher, 2025)
Global food waste (1.3 billion tons per year) is a major economic and environmental issue, contributing considerably to cash losses and greenhouse gas emissions. This study assesses the efficacy, limitations, and integration potential of four Industry 4.0 technologies—IoT sensors, AI/ML algorithms, advanced active packaging, and blockchain traceability—for waste reduction at key food supply chain stages (production, logistics, retail, and consumption). We show that each technology has different waste reduction advantages using a rigorous literature synthesis (2020-2025), techno-economic evaluation, and environmental impact analysis. Crucially, coordinated deployment unleashes synergistic potential, resulting in considerably larger systemic waste reduction than standalone applications. However, fulfilling this promise requires overcoming long-standing obstacles such as implementation costs, data needs, recyclability issues, and energy usage. The results highlight the need for coordinated policy frameworks that promote interoperable technology, standardized data protocols, and circular design principles. This study outlines a systematic approach for changing food waste from a systemic failure to a controllable engineering issue, resulting in more resilient and efficient food systems.